STUDENTS’ DIFFICULTY IN WRITING ENGLISH: AFFECTED BY VOCABULARY SKILLS - Citra Anistasya (STKIP PGRI Lubuklinggau, 2022)
The title of this study “Students’ Difficulty in Writing English : Affected by Vocabulary Skills” or to create a sentence is to understand or how vocabulary skills affect high school students. The subject of this survey consists of second level students from SMA Raksana Medan. There were 40 students. Most of them were sampled of this study. The data in this study were obtained through test writing or sentence formation and were the most difficult compared to cognitive difficulties (organizational and mechanical aspects). In english, there are four skills in English (speaking, writing, listening and reading). Writing is one of important component of English skills that concerned by English teachers in SMA Raksana Medan. Writing relate on every teaching and learning activities in English. There are some difficulties and challenges on writing english. Especially, this study focused on how vocabulary skill give problems or difficulties impact on writing english.